Conservação de nascentes e análise integrada da paisagem em vertente urbana de Chapada dos Guimarães-MT - Araújo, Lucas Neris (2024)
The intensification of the urbanization process in Brazilian cities generates numerous socio-environmental concerns, among which we can highlight the availability of drinking water for public supply. However, such problems affect the urban population differently, depending on the social class they belong to, considering that the quality of housing and public services, from a capitalist perspective, is conditioned on the availability of resources to pay. The municipality of Chapada dos Guimarães is known nationally for its tourist attractions and scenic beauty evidenced by the geoecological context in which it is located. However, the same attractions, the warm climate and, among others, added to the proximity to the state capital have driven a great demand for lots and residences for the first and second homes of the Cuiabana middle class, causing a process of expansion of the urban fabric. in a diffuse, fragmented way and without the necessary urban infrastructure to guarantee the quality of life of the working population of Chapa and the protection of water bodies that are fundamental to the supply of water on the surface. Thus, the study aimed to analyze the characteristics of the physical, biotic environment and urban territorialities of a sector of the Coxipó River basin, located in the urban area of Chapada dos Guimarães-MT, focusing on the conservation of river springs. lower compartment (low slope). The research exposes how the weaknesses of environmental and urban legislative instruments predispose springs and Permanent Preservation Areas and, consequently, residents to impacts resulting from the expansion of the urban area. From the integrated analysis of the elements of the landscape under study, supported by official data, field campaigns and an aerial survey carried out with a remotely piloted aircraft, the neglect of springs, their environmental characteristics and the areas of permanent preservation associated with the set were revealed. of laws and official studies that support urban planning and territorial ordering of the city and the contribution of public authorities in the process of socio-spatial fragmentation of the city. It is hoped that the reflections raised in this work can contribute to the urban planning of Chapada dos Guimarães, in order to reconcile geo environmental potentialities and limitations, with a view to preserving the springs studied and improving the quality and living conditions of the working population residing in the municipality.